2015
DOI: 10.1016/j.bjhh.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Acute lymphoblastic leukemia in children and adolescents: prognostic factors and analysis of survival

Abstract: ObjectiveTo describe the clinical and laboratory features of children and adolescents with acute lymphoblastic leukemia treated at three referral centers in Ceará and evaluate prognostic factors for survival, including age, gender, presenting white blood cell count, immunophenotype, DNA index and early response to treatment.MethodsSeventy-six under 19-year-old patients with newly diagnosed acute lymphoblastic leukemia treated with the Grupo Brasileiro de Tratamento de Leucemia da Infância – acute lymphoblastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
54
0
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(92 citation statements)
references
References 22 publications
23
54
0
15
Order By: Relevance
“…Age and gender. The mean age group of our study is slightly older than the (3-6) years reported by the Multi-Institutional International Collaborative Study (CALLME1) by the Middle East Childhood Cancer Alliance (MECCA) in which they comprised 33.8% 6 , older than what was found in the US of (1-4) years comprising (42.9%) 11,12 , and one international study that covered 184 countries which found the peak age to be (0-4) www.nature.com/scientificreports www.nature.com/scientificreports/ years 13 , but was close to the age reported in the Tehran study with a mean age of 5.5 years 14 and a Brazilian study which had the average age of diagnosis of 6.3 ± 0.5 years 15 . Gender ratio of M/F in our study was (1.56:1) which was slightly higher than the CALLME1 study (1.4:1), the US study (1.35:1), the international study (1.4:1), and the Tehran study (1.32:1), but lower than what was found in the Brazilian study (1.9:1) but there was no significant difference (P > 0.05) when comparing our study with all previous studies.…”
Section: Discussionsupporting
confidence: 51%
“…Age and gender. The mean age group of our study is slightly older than the (3-6) years reported by the Multi-Institutional International Collaborative Study (CALLME1) by the Middle East Childhood Cancer Alliance (MECCA) in which they comprised 33.8% 6 , older than what was found in the US of (1-4) years comprising (42.9%) 11,12 , and one international study that covered 184 countries which found the peak age to be (0-4) www.nature.com/scientificreports www.nature.com/scientificreports/ years 13 , but was close to the age reported in the Tehran study with a mean age of 5.5 years 14 and a Brazilian study which had the average age of diagnosis of 6.3 ± 0.5 years 15 . Gender ratio of M/F in our study was (1.56:1) which was slightly higher than the CALLME1 study (1.4:1), the US study (1.35:1), the international study (1.4:1), and the Tehran study (1.32:1), but lower than what was found in the Brazilian study (1.9:1) but there was no significant difference (P > 0.05) when comparing our study with all previous studies.…”
Section: Discussionsupporting
confidence: 51%
“…These findings are similar to other reports where a large proportion of ALL patients are classified for having severe anemia. 12,15 Leukocytosis is commonly presented in ALL patients. Similarly to the findings in Iran and Brazil, where most patients have leukocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…17 Similarly founded in Brazil where the majority of their ALL patients have thrombocytopenia. 15 The differentiation process of lymphoid cells is blocked in ALL patients, while their production and proliferation are uncontrolled, which result in blast cells findings in peripheral blood smear and bone marrow. ALL can be presumed with blast cells count results >5%, however for definite diagnosis of ALL, 20% blast cells or more is needed.…”
Section: Discussionmentioning
confidence: 99%
“…(14-18) The most valuable markers, for their predictive value, are the immunological and biomolecular features of the leukemic cells. (19)(20)(21) The identification of fusion genes was used for risk stratification and as prognostic markers. Genetic anomalies were found in 25.7% of the patients enrolled in this study.…”
Section: Discussionmentioning
confidence: 99%